Talking relative age effects: a fictional analysis based on scientific evidence - Roberts, S. J. (Asia Pacific Journal of Health, Sport and Physical Education, 2014)
During the past 30 years, there has been a considerable amount of scientific attention dedicated to the reported age discrimination which occurs in youth and elite sport. The purpose of this paper is to examine the notion of relative age effects (RAEs) through a slightly different lens. This paper therefore presents a fictional conversation between Jim, a sport and exercise scientist, Paul, a professional football coach, and Helen, a coach education manager. The conversation takes place following a presentation on the nuances of the RAE phenomenon at a National Sports Coaching Conference. The debate is driven by Paul's Darwinian approach to the existence (or not) of RAEs and Helen's concerns that sports administrators responsible for talent identification and development within national governing bodies of sport are not raising awareness of this phenomenon with the sports coaches who are ultimately responsible for talent development in youth sport.